SERUM LEVELS OF CARDIAC ENZYMES IN MATURE DOGS WITH CARDIOVASCULAR DISEASE - Pino V., Oswaldo (2008)
Serum levels of the asparte amino transferase (AST), creatine kinase (CK), the MB fraction of creatine kinase (CK-MB) and lactate dehydrogenase (LDH) enzymes were measured in adult dogs with cardiovascular disease to evaluate their potential use as predictors of myocardial damage in heart failure. Twenty five animals, irrespective of sex and breed, were studied: 10 of them were apparently healthy (G1) and the other 15 suffered of cardiovascular illnesses (G2). Blood samples were collected and the resulting sera was examined by spectrophotometry. The results indicated that only levels of CK-MB were statistically different (p<0.05) betwen the two groups. It is concluded that CK-MB can be used to predict progressive myocardial damage in dog´s heart failure.